2011
DOI: 10.5897/ajb11.1582
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extrusion parameters on some properties of dietary fiber from lemon (Citrus aurantifolia Swingle) residues

Abstract: Approximately 50% of the original whole fruit mass, after citrus processing for juice, consist of the peel, membranes and seeds. Citrus residues consist mainly of insoluble fiber (celluloses) and a small proportion of soluble fiber (hemicelluloses and pectin). For this reason, citrus residues could be considered as a potential high fiber ingredient that is used for food industry. In this study, lemon residues were extruded to modify and increase their soluble fiber fraction. Surface response methodology with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 7 publications
1
0
0
1
Order By: Relevance
“…They observed a slight reduction in TDF content for all treatments; however, a maximum increase of 89% on the SDF fraction (from 20.1 to 37.9 g•100 g −1 dm, untreated and extruded, respectively) was achieved when processing the feedstock at 35% moisture, 150°C, and 140 rpm. A similar trend was observed by Méndez-García et al (2011) who found an increment of up to 30% of the SDF fraction in lime pomace (from 38.6 to 50.0 g•100 g −1 dm, untreated and extruded, respectively) extruded at 110°C and 30% moisture. Huang and Ma (2016) studied the effect of extrusion conditions in orange pomace using a single screw laboratory scale extruder (temperature 115-135°C, feeding moisture 10-18%, and screw speed 230-350 rpm).…”
Section: Modification Processes Of the Composition And Functionality supporting
confidence: 86%
“…They observed a slight reduction in TDF content for all treatments; however, a maximum increase of 89% on the SDF fraction (from 20.1 to 37.9 g•100 g −1 dm, untreated and extruded, respectively) was achieved when processing the feedstock at 35% moisture, 150°C, and 140 rpm. A similar trend was observed by Méndez-García et al (2011) who found an increment of up to 30% of the SDF fraction in lime pomace (from 38.6 to 50.0 g•100 g −1 dm, untreated and extruded, respectively) extruded at 110°C and 30% moisture. Huang and Ma (2016) studied the effect of extrusion conditions in orange pomace using a single screw laboratory scale extruder (temperature 115-135°C, feeding moisture 10-18%, and screw speed 230-350 rpm).…”
Section: Modification Processes Of the Composition And Functionality supporting
confidence: 86%
“…Las investigaciones presentadas en la Tabla 11 demuestran la aplicabilidad de los concentrados de fibra dietética en el país en diversos productos. La mayor parte de las cáscaras de frutas más cultivadas en el país y de las aplicadas en la fabricación de bebidas contienen valores iguales o superiores al 40 % en fibra dietética, siendo la cáscara de limón la más alta con 95,61 % (Méndez et al, 2011), lo que las hace una fuente importante de recursos para la creación de ingredientes alimentarios, sien do así se debería profundizar en su aplicabilidad en productos y en el estudio de sus propiedades según el tipo de fruta. El contenido de humedad, ceniza, grasa, proteína, carbohidratos y fibra en concentrados de fibra dietética obtenidos del procesamiento de cáscaras de fruta cambia según la fruta, lugar de cultivo y estado de maduración.…”
Section: Estudios De Aplicaciones De Concentrados De Fibra En El Paísunclassified